Vegetation description of the Doornhoek section of the Mountain Zebra National Park (MZNP), South Africa - Hugo Bezuidenhout; Leslie R. Brown (Koedoe: African Protected Area Conservation and Science, 2008)
The Mountain Zebra National Park (MZNP) has been extended over the last couple of years. One of the newly procured areas is the Doornhoek section, which had been adjacent to the park. To develop scientifically sound management programmes for conservation areas, it is essential that an inventory of their natural resources be undertaken. The aim of this study was to classify, describe and map the vegetation of the Doornhoek section of the park. The floristic data were analysed in accordance with the Braun-Blanquet procedures using the BBPC suite. The data analysis resulted in the identification of eight communities, which can be grouped into seven major community types (Rhus lucida–Buddleja glomerata Shrubland, Rhigozum obovatum–Rhus longispina Shrubland, Helichrysum dregeanum–Aristida diffusa Grassland, Pentzia globosa–Enneapogon scoparius Grassland, Aristida adscensionus–Pentzia globosa Grassland, Cadaba aphylla–Acacia karroo Woodland and Lycium oxycarpum–Acacia karroo Woodland). Four of these communities occur on the higher-lying plateau, mid-slope and crest areas, while the other four communities are located on the lower-lying mid-plateau and foot slope, along drainage lines and in valley-bottom areas. The description of the plant communities, together with the vegetation map, can serve as a basis for formulating a management programme for the larger park. Although sections of Doornhoek have been overgrazed and degraded in the past, its recent addition to the MZNP contributes to the available habitat preferred by large herbivores, such as valley bottoms, foot-slopes and plateaux.